Autosomal recessive idiopathic epilepsy in an inbred family from Turkey: Identification of a putative locus on chromosome 9q32-33 - GÜNEY, AHMET İLTER (WILEY, 2004)
Purpose: The study describes the clinical features of an inbred family from Turkey with three members affected by seizures and tests possible autosomal recessive (AR) inheritance by means of linkage analysis. Methods: Personal and family history was obtained from each subject, and general physical, neurologic, and EEG examinations were performed. A set of 382 fluorescence-labeled markers was used for the initial genome-wide search. A further set of 83 markers was used to map the locus precisely and to exclude the remaining genome. Results: Twelve individuals from three generations were examined. Two subjects were affected by idiopathic epilepsy, whereas, their brother experienced a single unprovoked generalized seizure. Two siblings affected by idiopathic epilepsy and their unaffected sister showed a photoparoxysmal response to photic stimulation. Nine family members reported migraine. The genome-wide search led to the identification of a unique homozygous, 15.1-cM region shared by subjects with seizures on chromosome 9q32-33 and providing a lod score of 2.9. This locus, however, was not associated with migraine in this pedigree. Conclusions: The study suggests that idiopathic epileptic traits with AR inheritance might be underestimated in the general population and that inbred pedigrees may represent powerful tools for the identification of AR genes.
Keywords: idiopathic; epilepsy; autosomal recessive inheritance; inbred families; FEBRILE SEIZURES PLUS; MYOCLONIC EPILEPSY; ROLANDIC EPILEPSY; GENERALIZED EPILEPSY; SODIUM-CHANNEL; GENE; MIGRAINE; MUTATIONS; CHILDHOOD; DISORDER